Basic Aspects of Seasonal Cardiovascular Mortality - G. F. Andreeva (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2021)
The review demonstrates the main aspects of seasonal cardiovascular mortality. Climatic factors, including seasonal weather changes, have a significant impact on the biosphere. People are also characterized by the seasonal dynamics of the activity of many organs and systems, biochemical parameters, and mortality. Cardiovascular mortality is also characterized by seasonal fluctuations: in winter it is maximum, in summer it is minimal. The same patterns are characteristic of mortality from cardiovascular diseases (myocardial infarction, stroke, cardiac arrhythmias, etc.). The article presents the basic patterns of seasonal cardiovascular mortality in various climatic zones, the cardiovascular mortality of countries located in the equatorial and subequatorial climatic region. In addition, the mortality displacement phenomenon, the paradox of winter mortality. The main trends in changes in cardiovascular mortality over a long period of time are demonstrated. The paper discusses some of the mechanisms that underlie the dynamics of cardiovascular mortality during the year: seasonal fluctuations in the level of vitamin D, lipids in the blood plasma, changes in hemodynamic parameters, the effects of microbial and viral infections in the cold season, etc. In addition, data on seasonal the dynamics of risk factors for cardiovascular diseases is considered: an increase in body weight, a physical activity decrease, a change in the nutrition structure in the winter, the seasonal dynamics of depression, anxiety, hostility, the relationship of seasonal cardiovascular mortality with socio-economic, demographic and other factors. In conclusion, the main ways of development and prevention of seasonal CV cardiovascular mortality M, taking into account modern technologies at the international level, for state health departments, for specific patients, are demonstrated.